O direito das autoridades públicas transnacionais: uma perspectiva crítica sobre questões de legitimação - Flores, Maurício Pedroso (Universidade do Vale do Rio dos Sinos, 2023)
As transnational public authorities have been established as institutions of governance of significant relevance within different regulatory areas and issues, their actual exercise of power raises questions about their legitimacy conditions. Resort to traditional reasonings about validity of law, that largely supports the view that states and interstate organizations are legitimate, are unavailable to these authorities. Since they cannot explain their exercise of authority either on the basis of state law or through classical international law, new forms of legitimation need to be assessed. The main objective of this thesis is to show that these forms can still be investigated from a legal theory perspective, insofar it abandons some assumptions traditionally linked to statist legal views. Thus, the first chapter seeks to establish a legal perspective compatible with the emergence of transnational legal phenomena. The conceptions of legal meaning and multinormativity play a central role in the argument. Then, second chapter expands its legal theory perspective to take account of the interdisciplinary debates over legitimation issues of different global governance institutions. The observations made in this part culminate in the establishment of a coherent vision with the methodology adopted by this work, which is the Frankfurtian-inspired Critical Theory. Finally, third chapter goes more specifically into the regulatory dynamics of transnational public authorities, and addresses possible relationships between law and legitimacy within it based on five themes regarded as central in light of the multinormative and critical legal vision that we have developed in the previous chapters: institutional designs, legitimation procedures, rule of law, democracy and the idea of emancipation.
Keywords: Autoridades públicas transnacionais; Governança global; Legitimação; Teoria Crítica; Teoria do direito; Critical theory; Global governance; Legal theory; Legitimation; Transnational public authorities; ACCNPQ::Ciências Sociais Aplicadas::Direito